PENGARUH BRAND AWARENESS WARDAH TERHADAP CORPORATE IMAGE PT PARAGON TECHNOLOGY AND INNOVATION: (Survei Eksplanatif Followers Instagram @wardahbeauty pada Periode Maret - Juni 2025) - Amellia Putri; Wina Puspita Sari; Asep Soegiarto; Muria Putriana; Qoryna Noer Seyma El Farabi (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
Increasingly fierce competition in the cosmetics industry in Indonesia encourages companies to increase brand awareness as part of a communication strategy in shaping a strong corporate image. Researchers conducted this study to determine the effect of Wardah Brand Awareness on PT Paragon Technology and Innovation's Corporate Image. This research uses a quantitative approach with an online survey method involving 100 respondents, namely followers of the @wardahbeauty Instagram account. Researchers analyzed the data using the Pearson correlation test and simple linear regression. The results of the analysis show that there is a significant influence between Brand Awareness and Corporate Image, with a significance value of 0.000 (<0.05). The Pearson correlation coefficient value of 0.590 indicates a fairly strong positive relationship between the two variables. In addition, the R Square value of 0.349 indicates that Brand Awareness affects 34.9% of the variation in Corporate Image, while the remaining 65.1% is influenced by other factors. This finding concludes that the higher the level of Wardah Brand Awareness, the more positive the public perception of the company's image. This study recommends that PT Paragon Technology and Innovation strengthen its brand communication strategy through more massive digital campaigns and develop Corporate Social Responsibility (CSR) programs to build public trust in a sustainable manner. Keywords: brand awareness, corporate image, communication strategy, Wardah, PT Paragon Technology and Innovation